Manifestations of Personification is Simile - سید محمدرضا ابن‌الرسول; سید محمدهادی حسینی (مطالعات زبانی و بلاغی)
Personification (giving personality) gets manifestation in utterances with other literary techniques as simile which is its renewal. By a glance on eloquent prose and poem, the study tries to consider manifestation of personification in simile. The manifestation of personification in simile takes place through point of similarity (within simile) or nominative and address (from outside). After a short glance on personification, the authors have considered its accompaniment with simile through a new angle.